2019
DOI: 10.18632/oncotarget.26608
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen in the tumor microenvironment: effects on dendritic cell function

Abstract: Solid tumors grow at a high speed leading to insufficient blood supply to tumor cells. This makes the tumor hypoxic, resulting in the Warburg effect and an increased generation of reactive oxygen species (ROS). Hypoxia and ROS affect immune cells in the tumor micro-environment, thereby affecting their immune function. Here, we review the known effects of hypoxia and ROS on the function and physiology of dendritic cells (DCs). DCs can (cross-)present tumor antigen to activate naive T cells, which play a pivotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 135 publications
2
50
0
Order By: Relevance
“…1A). Our results indicated that hypoxic conditions of the subcutaneously injected cryogel suppress DC activation, which is consistent with previous reports 15,16 . Therefore, we engineered oxygen-generating cryogels (O 2 -Cryogels) to mitigate hypoxia-driven immunosuppression 17 .…”
supporting
confidence: 94%
“…1A). Our results indicated that hypoxic conditions of the subcutaneously injected cryogel suppress DC activation, which is consistent with previous reports 15,16 . Therefore, we engineered oxygen-generating cryogels (O 2 -Cryogels) to mitigate hypoxia-driven immunosuppression 17 .…”
supporting
confidence: 94%
“…With respect to dendritic cells (DCs), contradictory effects of hypoxic TME with excessive ROS have been reported [94]. Despite the effect of hypoxia and ROS in the upregulation of a plethora of pro-inflammatory cytokines, both hypoxia and ROS stimulate migration of immature but prevent migration of mature-DCs resulting in an immunosuppressive TME.…”
Section: Effects Of Tumor Microenvironment (Tme) Metabolism On Immunementioning
confidence: 99%
“…Despite the effect of hypoxia and ROS in the upregulation of a plethora of pro-inflammatory cytokines, both hypoxia and ROS stimulate migration of immature but prevent migration of mature-DCs resulting in an immunosuppressive TME. These lead to limited influx and maturation of immature DCs to the TME while the egress of activated DCs to lymphoid system is prevented, limiting the function of DCs in presenting tumor antigens to activate T lymphocytes, [94].…”
Section: Effects Of Tumor Microenvironment (Tme) Metabolism On Immunementioning
confidence: 99%
“…Nonetheless, systemic or local administration alone has not succeeded to eliminate tumours, and the mechanism by which hydrogen peroxide therapy produces anti-tumour effects is still debated. Owing to the homeostatic role of immune cells in maintaining the integrity of every tissue, these cells tend to localize at the tumour loci (26). Subsequently, immune cells adapt to the hypoxic conditions found in the tumour microenvironment and can protect and support cancerous tissues and tumour cells (27,28).…”
Section: Introductionmentioning
confidence: 99%